Acute and delayed implantation of positively charged 2-hydroxyethyl methacrylate scaffolds in spinal cord injury in the rat - Hejcl, Ales; Urdzikova, Lucie; Sedy, Jiri; Lesny, Petr; Pradny, Martin; Michalek, Jiri; Burian, Martin; Hajek, Milan; Zamecnik, Josef; Jendelova, Pavla; Sykova, Eva (Journal of neurosurgery. Spine, 2008)
OBJECT: Hydrogels are nontoxic, chemically inert synthetic polymers with a high water content and large surface area that provide mechanical support for cells and axons when implanted into spinal cord tissue. METHODS: Macroporous hydrogels based on 2-hydroxyethyl methacrylate (HEMA) were prepared by radical copolymerization of monomers in the presence of fractionated NaCl particles. Male Wistar rats underwent complete spinal cord transection at the T-9 level. To bridge the lesion, positively charged HEMA hydrogels were implanted either immediately or 1 week after spinal cord transection; control animals were left untreated. Histological evaluation was performed 3 months after spinal cord transection to measure the volume of the pseudocyst cavities and the ingrowth of tissue elements into the hydrogels. RESULTS: The hydrogel implants adhered well to the spinal cord tissue. Histological evaluation showed ingrowth of connective tissue elements, blood vessels, neurofilaments, and Schwann cells into the hydrogels. Morphometric analysis of lesions showed a statistically significant reduction in pseudocyst volume in the treated animals compared with controls and in the delayed treatment group compared with the immediate treatment group (p < 0.001 and p < 0.05, respectively). CONCLUSIONS: Positively charged HEMA hydrogels can bridge a posttraumatic spinal cord cavity and provide a scaffold for the ingrowth of regenerating axons. The results indicate that delayed implantation can be more effective than immediate reconstructive surgery.
Keywords: Animals; Methacrylates; tkáňové podpůrné struktury; Rats; Cysts; Connective Tissue; Rats, Wistar; axony; biokompatibilní materiály; Spinal Cord; methakryláty; Wound Healing; Schwannovy buňky; Time Factors; časové faktory; Guided Tissue Regeneration; Hydrogels; mícha; poranění míchy; řízená tkáňová regenerace; cysty; pojivová tkáň; regenerace nervu; Biocompatible Materials; Nerve Regeneration; Spinal Cord Injuries; Neurofibrils; Male; modely nemocí na zvířatech; hydrogely; hojení ran; Disease Models, Animal; krysa rodu Rattus; paraplegie; Schwann Cells; zvířata; mužské pohlaví; Tissue Scaffolds; Paraplegia; neurofibrily; potkani Wistar; Axons